Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00163-003-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Information hiding in product development: the design churn effect

Abstract: Execution of a complex product development project is facilitated through its decomposition into an interrelated set of localized development tasks. When a local task is completed, its output is integrated through an iterative c ycle of system-wide integration activities. Integration is often accompanied by inadvertent information hiding due to the asynchronous information exchanges.We show that information hiding leads to persistent recurrence of problems (termed as the design churn effect) such that progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(132 citation statements)
references
References 26 publications
7
125
0
Order By: Relevance
“…This characteristic reduces the amount and range of potential revisions that occur in the dynamic PD process, and thus increases the likelihood of converging to a successful solution. This empirical observation is found to be consistent with the dynamic PD model (using linear systems theory) developed in [5].…”
Section: B In-degree and Out-degree Distributionssupporting
confidence: 84%
See 3 more Smart Citations
“…This characteristic reduces the amount and range of potential revisions that occur in the dynamic PD process, and thus increases the likelihood of converging to a successful solution. This empirical observation is found to be consistent with the dynamic PD model (using linear systems theory) developed in [5].…”
Section: B In-degree and Out-degree Distributionssupporting
confidence: 84%
“…The high clustering coefficient of PD networks suggests an inherently modular organization of PD processes; i.e., the organization of the PD process in clusters that contain most, if not all, of the interactions PHYSICAL REVIEW E 69, 016113,2004 internally and the interactions or links between separate clusters is eliminated or minimized [1][2][3]. The dynamic model developed in [5] shows that a speed up of the PD convergence to the design solution is obtained by reducing or 'ignoring' some of the task dependencies (i.e., eliminating some of the arcs in the corresponding PD network). A modular architecture of the PD process is aligned with this strategy.…”
Section: Legendmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, they have shown that the robustness and stability of complex engineering systems is closely linked with the existence of hubs, and that the network behaviour is sensitive to its structure. In addition, eigenstructure or eigenvector analysis has been used for identifying key features in the engineering design iterations in (Smith and Eppinger 1997) and for exploring some hiding information in the complex product development projects in (Yassine et al 2003).…”
Section: Introductionmentioning
confidence: 99%